The Effectiveness of the Management of the Modern Tax Administration System at the Soppeng Regency Samsat Office - Nur Asmi; Sirajuddin Saleh; Nasaruddin Hasyim (Asha Publishing, 2025)
The purpose of this study is to evaluate how well the Soppeng Regency Samsat Office manages its contemporary tax administration system. Because this research is qualitative, data collection methods that include observation, interviews, recordings and documentation can be used to achieve research objectives. Based on the results of this study, it shows that the effectiveness of the management of the modern tax administration system at the Soppeng Regency Samsat Office can be seen from the indicators of organizational restructuring, technology improvement, improvement of human resource management, and the implementation of good governance has been